Plecstatin-1 induces an immunogenic cell death signature in colorectal tumour spheroids. Issue 12 (9th December 2020) - Wernitznig, Debora; Meier-Menches, Samuel M.; Cseh, Klaudia; Theiner, Sarah; Wenisch, Dominik; Schweikert, Andreas; Jakupec, Michael A.; Koellensperger, Gunda; Wernitznig, Andreas; Sommergruber, Wolfgang; Keppler, Bernhard K.
Abstract : Treatment with plecstatin-1 resulted in disruption of the cytoskeleton and phosphorylation of the stress marker eIF2α, and induction of an immunogenic cell death signature, including calreticulin, high mobility group protein B and extracellular ATP. Abstract : Organometallic metal(arene) anticancer agents were believed to confer low selectivity for potential cellular targets. However, the ruthenium(arene) pyridinecarbothioamide (plecstatin-1) showed target selectivity for plectin, a scaffold protein and cytolinker. We employed a three-dimensional cancer spheroid model and showed that plecstatin-1 limited spheroid growth, induced changes in the morphology and in the architecture of tumour spheroids by disrupting the cytoskeletal organization. Additionally, we demonstrated that plecstatin-1 induced oxidative stress, followed by the induction of an immunogenic cell death signature through phosphorylation of eIF2α, exposure of calreticulin, HSP90 and HSP70 on the cell membrane and secretion of ATP followed by release of high mobility group box-1.